PENGALAMAN BERDUKA PASCA PERISTIWA BUNUH DIRI IBU - Nabila Ratu; Yohanis Franz La Kahija (Jurnal EMPATI, 2017)
In this modern era, suicide holds status as one of the biggest public health problems in the world. According to data compiled by the World Health Organization (WHO), in 2015 there were 788,000 deaths from suicide worldwide. A phrase "suicide survivor" is referred to a person who experiences grief over the death of a loved one by suicide. This study aims to understand the grief experience of a child after the loss of mother due to suicide. This study includes an intensive look at grief experience to understand how the grief experienced by children after the mother's loss due to suicide, how children gave meaning of the grief experience and what process that led to child’s recovery. This is a qualitative study processed by Interpretative Phenomenological Analysis (IPA) technique. Data were obtained with semi-structured interview techniques. There are three main themes found: the relationships with mother, the dynamics of dealing with loss and the process towards recovery.